Climate congruence: How espoused psychosocial safety climate and enacted managerial support affect emotional exhaustion and work engagement - Yulita, -; Dollard, M.F.; Idris, M.A. (Elsevier, 2017)
The alignment between espoused (saying) and enacted (doing) psychosocial safety climate (PSC; a climate for worker psychological health) is important to consider in relation to health and work outcomes. This diary study explored the interplay (moderation and mediation processes) between espoused PSC (organizational level PSC) and daily enacted PSC (operationalized in the specific domain of managerial support) and their relationships to worker psychological health (i.e., daily emotional exhaustion) and motivation (i.e., daily work engagement). In all, 545 diary data points were collected within five consecutive days from 109 secondary school teachers across 23 schools in Selangor, Malaysia. Using Hierarchical Linear Modeling (HLM) in a three-level model, we found espoused PSC was positively related to daily enacted managerial support. For work engagement, espoused PSC was related to work engagement through enacted managerial support. For emotional exhaustion, enacted managerial support moderated the negative relationship between espoused PSC and daily emotional exhaustion. The expected (beneficial) effects of espoused PSC were evident when high levels aligned with high levels of enacted managerial support within schools. In this case, PSC acts as a safety signal — when high espoused PSC is coupled with repeated, unequivocal and stable support (enacted managerial support), employees may feel safe to take action in their environment to protect themselves from emotional exhaustion. These findings offer new insights regarding how managers can build PSC, by valuing employee psychological health, and translating PSC into action (integrity in saying and doing), to increase psychological health and work engagement.